Algorithmic learning theory 22nd International Conference, ALT 2011, Espoo, Finland, October 5-7, 2011. Proceedings - Kivinen, Jyrki; Szepesvári, Csaba; Ukkonen, Esko; Zeugmann, Thomas (Springer eBook., 2011)
This book constitutes the refereed proceedings of the 22nd International Conference on Algorithmic Learning Theory, ALT 2011, held in Espoo, Finland, in October 2011, co-located with the 14th International Conference on Discovery Science, DS 2011. The 28 revised full papers presented together with the abstracts of 5 invited talks were carefully reviewed and selected from numerous submissions. The papers are divided into topical sections of papers on inductive inference, regression, bandit problems, online learning, kernel and margin-based methods, intelligent agents and other learning models.